A Real-time and Non-Intrusive Analyzer for Anomalous Behavior of Computer Networks with Paraconsistent Logic (INFOCOMP Journal of Computer Science, 2018)
Anomalous behavior in computer networks is always a challenge when a great number of connected devices is considered, as well as the issue of privacy when direct access to the equipment is necessary. Computer viruses, intrusion tools, or malicious programs can produce unexpected changes in a computer network, due to the unusual behavior, if compared to normal operating situations. Therefore, searching for anomalies in the network, which can be understood as situations of inconsistency in several measures of performance of the analyzed devices, should be considered. A possible approach in such situations is the use of a non-classical logic. The Paraconsistent Logic is one of these and it has been increasingly used in several areas for its flexibility and ease. It can determine several additional states, beyond true and false, to deal with situations of inconsistency. This project proposes a new alternative in the search for anomalies in computer networks with Paraconsistent Logic through a non-intrusive approach.